Can Patient Effort Influence Sensitivity & Specificity of the Gravity Stress View? Assessing the Potential for False Negative Results. Issue 4 (22nd October 2020) - Broughton, Kimberly K.; Miller, Christopher P.; Williams, Caroline; Stupay, Kristen L.; Kwon, John Y.
Category: Ankle; Trauma Introduction/Purpose: In the setting of apparently isolated distal fibula fractures, the radiographic gravity stress view (GSV) has been validated as a reliable method to determine mortise stability. Based on previous studies demonstrating that plantarflexion can increase the measured medial clear space (MCS), patients are often asked to actively hold their ankle in a neutral position. However, it has not been studied whether dynamic muscle activation in the form of attempted dorsiflexion and/or supination can reduce and realign an unstable mortise. If these efforts can overcome gravity, resultant images could lead to a false negative result and missed diagnosis of instability. The goal of the present investigation is to determine if active effort by the patient can influence MCS measurements in proven unstable bimalleolar-equivalent ankle fractures. Methods: Eighteen consecutive patients with apparently isolated distal fibula fractures (Weber-B type) identified on initial nonweightbearing radiographs were assessed for mortise stability with a standard, unassisted GSV. If the radiograph demonstrated MCS widening > 4 mm, 3 additional views were performed: GSV with an assistant manually maintaining the ankle in a neutral position; GSV with the patient actively dorsiflexing the ankle to the same neutral position; and GSV with the patient actively dorsiflexing and supinating the foot to the same neutral position. All radiographs were digitally obtained and measured using a DICOM measurement tool. The MCS was measured by the senior author (JYK) who was blinded to the nature of the ankle position. Statistical analysis of the data was then conducted. Results: Of the eighteen patients who met inclusion criteria, the mean age was 48.9 years (range: 22-85, SD=18.9). Twelve patients (66%) were female and six (33%) were male. The laterality was evenly split with nine patients presenting with a right ankle injury and nine left ankles. The data was non-parametric; therefore, a Friedman's test was utilized for analysis between the different MCS measurements per patient. There was no statistically significant difference in the measured MCS in any of the three tested scenarios, χ2(2)=4.261, p=0.119. Only 5 of 18 subjects had any measurable decrease in their MCS when asked to supinate their foot. Of these 5, the maximum reduction was 1.21mm. The remainder of patients had an increase in MCS ranging from 0.1 to 4.0mm. Conclusion: This investigation supports the notion that the gravity stress test is unlikely to yield false negative results when patients attempt to actively maintain a neutral ankle position during imaging. There was a non-significant inverse trend indicating that dynamic effort may in fact further displace the mortise as indicated by an increased MCS in several study participants, rather than reduce it. Thus, one can conclude that despite voluntary effort, patients with bimalleolar-equivalent ankle fractures are unlikely able to overcome the effect of gravity on the unstable mortise.